2021
DOI: 10.3389/fphar.2021.640441
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prokineticin 2 in Oxidative Stress and in Neuropathological Processes

Abstract: The prokineticin (PK) family, prokineticin 1 and Bv8/prokineticin 2 (PROK2), initially discovered as regulators of gastrointestinal motility, interacts with two G protein-coupled receptors, PKR1 and PKR2, regulating important biological functions such as circadian rhythms, metabolism, angiogenesis, neurogenesis, muscle contractility, hematopoiesis, immune response, reproduction and pain perception. PROK2 and PK receptors, in particular PKR2, are widespread distributed in the central nervous system, in both neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Despite the deleterious effects demonstrated for chemokines in NP, there are recent literature studies that suggest a neuroprotective role of some chemokines in other pathological conditions [ 158 , 159 , 160 ]. For example, the chemokine CCL5 acting on a GPCR named GPR75 (G Protein-coupled Receptor 75), which does not belong to the chemokine receptor family and is expressed by neuronal cells, activates intracellular signaling pathways associated with neuroprotective effects [ 159 ].…”
Section: Neuropathological Mechanisms Underlying Neuropathic Painmentioning
confidence: 99%
“…Despite the deleterious effects demonstrated for chemokines in NP, there are recent literature studies that suggest a neuroprotective role of some chemokines in other pathological conditions [ 158 , 159 , 160 ]. For example, the chemokine CCL5 acting on a GPCR named GPR75 (G Protein-coupled Receptor 75), which does not belong to the chemokine receptor family and is expressed by neuronal cells, activates intracellular signaling pathways associated with neuroprotective effects [ 159 ].…”
Section: Neuropathological Mechanisms Underlying Neuropathic Painmentioning
confidence: 99%
“…The prokineticin system, involving the novel chemokine PK2 and its receptors PKR1 and PKR2, is involved in the pathogenesis of AD. It has been found that PK2 can act as a mediator of brain damage and that it plays a crucial role in amyloid-induced neuronal death [ 43 ]. Indeed, Aβ 1–42 increases the mRNA and protein levels of PK2/PKRs in vitro in primary cortical neurons (CNs), and the non-protein PKRs antagonist PC1 protects CNs from Aβ 1–42 -induced neurotoxicity in a dose-dependent manner by reducing PK2 overexpression.…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…Indeed, Aβ 1–42 increases the mRNA and protein levels of PK2/PKRs in vitro in primary cortical neurons (CNs), and the non-protein PKRs antagonist PC1 protects CNs from Aβ 1–42 -induced neurotoxicity in a dose-dependent manner by reducing PK2 overexpression. Moreover, the use of PC1 prevents the impairment of long-term potentiation (LTP) in the hippocampus of Tg2576 (TG, a transgenic mouse model of AD) mice compared to wild-type (WT) control mice and also reduces AMPA currents [ 43 ]. The same group showed in vivo that in a non-transgenic animal model of Alzheimer’s disease, induced by intracerebroventricular (i.c.v.)…”
Section: Neurological Diseasesmentioning
confidence: 99%
See 2 more Smart Citations